2012
DOI: 10.1007/s10531-011-0220-z
|View full text |Cite
|
Sign up to set email alerts
|

Species richness, taxonomy and peculiarities of the neotropical rust fungi: are they more diverse in the Neotropics?

Abstract: The species richness of rust fungi (Pucciniales or Uredinales) in the neotropics is reviewed. Species numbers are presented for all neotropical countries and rust-plantratios calculated. It is discussed whether the ratio for a given region can be explained by the species richness of vascular plants alone or whether it is caused by additional factors. In the first case, ratios should apply globally and vary only slightly; in the second case, more diverging ratios are expected. Observed ratios ranged between 1:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 102 publications
0
8
0
4
Order By: Relevance
“…A flora dos remanescentes florestais da RMB foi considerada por Amaral et al (2009) de alta riqueza de espécies endêmicas, mas Berndt (2012) argumenta que a riqueza de espécies de ferrugem não é impulsionada unicamente pela riqueza de espécies de plantas, mas sim pela composição da flora, em relação à porcentagem de famílias e gêneros de plantas hospedeiras de diferentes espécies de ferrugens. Isso pode explicar a menor riqueza de fungos no PEUTi, onde a riqueza de hospedeiras foi menor também em relação à EMBRAPA.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A flora dos remanescentes florestais da RMB foi considerada por Amaral et al (2009) de alta riqueza de espécies endêmicas, mas Berndt (2012) argumenta que a riqueza de espécies de ferrugem não é impulsionada unicamente pela riqueza de espécies de plantas, mas sim pela composição da flora, em relação à porcentagem de famílias e gêneros de plantas hospedeiras de diferentes espécies de ferrugens. Isso pode explicar a menor riqueza de fungos no PEUTi, onde a riqueza de hospedeiras foi menor também em relação à EMBRAPA.…”
Section: Resultsunclassified
“…Essas Famílias também constam como as mais ricas em hospedeiros em vários estudos nos diferentes continentes (Berndt 2012). Para o Bioma Amazônia, Sotão et al (2009) e França et al (2010 em estudos realizados no Pará e no Amapá, respectivamente, registraram estas famílias entre as mais representadas em número de ferrugens,e a família Bignoniaceae entre as de maior riqueza de ferrugem para a região Norte.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Whether these ratios hold up in tropical regions is indirectly assessed in the papers of Berndt (2012) and Mangelsdorff et al (2012) with sometimes conflicting results, highlighting the value of both sound taxonomic and monographic treatments as well as the need for more long-term fungal studies in tropical regions. For instance, the rust fungi (obligate plant pathogens) may be the best documented group of microfungi, yet Berndt (2012) found that ratios of known rust:plant species in Neotropical countries ranged from 1:16 to 1:124-no doubt a reflection, at least in part, of under sampling for fungi in most of these areas.…”
mentioning
confidence: 99%
“…Just as the study of Berndt (2012) shows that species data is unevenly distributed geographically, other papers in this issue show that there are, likewise, a number of specialized habitats that still remain to be fully assessed for tropical fungal diversity. These include fungi inhabiting insect guts, among which are Trichomycetes that have been reviewed by Lichtwardt (2012).…”
mentioning
confidence: 99%